Clinical practice guidelines for the management of liver metastases from extrahepatic primary cancers 2021. (12th December 2020) - Yamamoto, Masakazu; Yoshida, Masahiro; Furuse, Junji; Sano, Keiji; Ohtsuka, Masayuki; Yamashita, Shingo; Beppu, Toru; Iwashita, Yukio; Wada, Keita; Nakajima, Takako Eguchi; Sakamoto, Katsunori; Hayano, Koichi; et al.
Abstract: Background: Hepatectomy is standard treatment for colorectal liver metastases; however, it is unclear whether liver metastases from other primary cancers should be resected or not. The Japanese Society of Hepato‐Biliary‐Pancreatic Surgery therefore created clinical practice guidelines for the management of metastatic liver tumors. Methods: Eight primary diseases were selected based on the number of hepatectomies performed for each malignancy per year. Clinical questions were structured in the population, intervention, comparison, and outcomes (PICO) format. Systematic reviews were performed, and the strength of recommendations and the level of quality of evidence for each clinical question were discussed and determined. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to assess evidence and make recommendations. Results: The eight primary sites were grouped into five categories based on suggested indications for hepatectomy and consensus of the guidelines committee. Fourteen clinical questions were devised, covering five topics: (1) diagnosis, (2) operative treatment, (3) ablation therapy, (4) the eight primary diseases, and (5) systemic therapies. The grade of recommendation was strong for one clinical question and weak for the other 13 clinical questions. The quality of the evidence was moderate for two questions, low for 10, and very low for two. A flowchart was made to summarize the outcomes of the guidelines for the indications of hepatectomy and systemic therapy. Conclusions: These guidelines were developed to provide useful information based on evidence in the published literature for the clinical management of liver metastases, and they could be helpful for conducting future clinical trials to provide higher‐quality evidence. Abstract : Highlight The Japanese Society of Hepato‐Biliary‐Pancreatic Surgery created clinical practice guidelines for the management of metastatic liver tumors. The guidelines provide useful information based on evidence in the published literature for the clinical management of liver metastases, and they could be helpful for conducting future clinical trials to provide higher‐quality evidence.